Challenges In Teaching Arabic Language At Mas Ulumul Quran Langsa: A Case Study - Zuhafni Mawaddah; Azizah Hanum OK; Junaidi Arsyad (Institut Agama Islam An-Nawawi Purworejo, 2025)
MAS Ulumul Quran Langsa is a unique Islamic senior high school in Indonesia that integrates pesantren-based religious education with general education and a strong emphasis on science and technology (IPTEK). However, the teaching of the Arabic language at this institution faces several pedagogical challenges. This study aims to explore the core issues affecting Arabic language instruction at MAS Ulumul Quran Langsa and identify efforts to address them. This is a qualitative descriptive research employing a phenomenological approach. Data were collected through interviews, observations, and document analysis. The data analysis followed the Miles and Huberman model, and data validity was ensured through source triangulation. The findings reveal that the Arabic language teaching process at MAS Ulumul Quran Langsa is structured around core management functions. Nevertheless, several challenges persist, including: (a) students' limited comprehension of the material; (b) low learning motivation; (c) inadequate teacher competencies; and (d) suboptimal implementation of management functions. To overcome these challenges, the school has taken measures such as improving classroom instruction, enhancing student motivation, increasing teacher professional development, and reinforcing the application of educational management functions.